Study of Seismic Response Demands of Different L-shaped Buildings - Khanal, Bharat; Chaulagain, Hemchandra (Himalayan Journal of Applied Science and Engineering, 2020)
The present study evaluates the effect of plan configuration irregularity of different L shaped models. For this, one regular and six different L-shaped RC building frames were modeled for numerical analysis. The analysis was done through an equivalent static lateral force method and response spectrum analysis (dynamic analysis). The seismic response demands were measured in terms of story displacement, inter-story drift ratio, torsional irregularity ratio, and torsional diaphragm rotation. In addition, fundamental time period of structure, vibration mode shapes and modal participating mass ratios were also studied. The study shows that the fundamental time period of structure based on standard code shows a lower value as compared to a finite element approach. It is concluded that to account for the irregularities present within the buildings, current code provisions are insufficient and should be amended.